Archaeal Communities of South China Mangroves and Their Potential Roles in the Nitrogen Cycle. Issue 8 (1st August 2022) - Meng, Shanshan; Peng, Tao; Liu, Xiaobo; Pratush, Amit; Wang, Hui; Huang, Tongwang; Gu, Ji-Dong; Hu, Zhong
Abstract: Mangroves are unique ecosystems that harbor a wide variety of microbial communities including Archaea. Although Archaea have widely been reported to play important roles in biogeochemical cycles, the involvement of archaeal communities in mangrove ecosystems and nitrogen cycling remains largely underexplored. To bridge this gap, we investigated the distribution of archaeal communities and their functional genes involved in the nitrogen cycle in South China mangroves covering seven different geographical areas. Our results indicated that mangroves are an important reservoir of unclassified Archaea, and therefore these unique ecosystems could fuel important discoveries in the future. Moreover, total nitrogen, total carbon and nitrate concentrations were found to be critical drivers of archaeal community composition in these mangroves. Selective Archaea, particularly Crenarchaeota and Euryarchaeota, are the major contributors to nitrogen cycling in the mangroves, especially involved in nitrification. Taken together, our findings advance our understanding of Archaea-driven nitrogen cycling in mangrove ecosystems.